(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The aim of this paper is to perform analysis of existing practice of Quality Management (QM) and Total Quality Management (TQM) principles in Croatian Language Service Provider (LSP) companies in order to analyse the gap and suggest recommendations. In this case study, twelve SME Croatian LSP companies are analysed by number of employees, existing and missing workplaces, focused business market, offices, Quality Certificate ISO 9001:2015 (2015) and membership in professional organizations. The existing practice in LSP Croatian companies are analysed through 10 TQM (total quality management) principles using self-evaluation assessment. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.